The influence of rainfall intensity on soil loss mass from cellular confined slopes - Nazir, R. (Elsevier B.V., 2016)
Cellular confinement systems serve as effective solutions to any erosion control project. Small model confinements (triangular, circular, and rectangular) measuring 50, 100, and 150 mm, with a depth of 10 mm, were embedded in soil samples at slope angles of 30°, 40°, 50°, and 60°. The observed soil mass losses for the confined soil systems are much smaller. As a result, the size of confinement, rainfall intensity, and slope angle have a direct effect on the soil mass loss results. The triangular and rectangular confinement systems showed the lowest and highest soil loss masses, respectively. The slopes also failed much faster in the unconfined system than in the confined slope.